Polymorphisms of SLC19A1 80 G>A, MTHFR 677 C>T, and Tandem TS Repeats Influence Pharmacokinetics, Acute Liver Toxicity, and Vomiting in Children With Acute Lymphoblastic Leukemia Treated With High Doses of Methotrexate - Cwiklinska, Magdalena; Czogala, Malgorzata; Kwiecinska, Kinga; Madetko-Talowska, Anna; Szafarz, Malgorzata; Pawinska, Katarzyna; Wieczorek, Aleksandra; Klekawka, Tomasz; Rej, Magdalena; Stepien, Konrad; Halubiec, Przemyslaw; Lazarczyk, Agnieszka; et al. (Frontiers in Pediatrics, 2020)
Introduction: High dose methotrexate (HD-Mtx) is highly effective and significantly improves overall acute lymphoblastic leukemia (ALL) patients survival. The pharmacodynamics of Mtx depends on the polymorphism of genes encoding proteins engaged in the folate metabolism pathway. The aim of the current study is to determine the relationship between variants of folate metabolism-related genes and the frequency of acute toxicities of HD-Mtx. Material and Methods: A group of 133 patients aged 1.5–18.1 years (median: 6.3) was treated in accordance with the ALL-IC-2002 and ALL-IC-2009 protocols. The following polymorphisms were determined: 80 G>A SLC19A1 (solute carrier family 19 member 1; rs1051266) with direct DNA sequencing, as well as 677 C>T MTHFR (methylenetetrahydrofolate reductase; rs1801133) and the tandem repeats of the TS (thymidylate synthase) with PCR technique. HD-Mtx organ toxicities were evaluated based on the laboratory tests results and the National Cancer Institute criteria. Results: In patients with genotypes AA for SLC19A1 and CC or CT for MTHFR Mtx steady state concentrations (Css) and AUCinf were distinctly higher. In patients with genotype 3R/3R for TS initial elimination rate constant was significantly higher (P = 0.003). Patients receiving Mtx at the dose of 5 g/m2 had lower clearance (4.35 vs. 8.92 L/h/m2) as compared to the ones receiving 2 g/m2 that indicates non-linear Mtx elimination at the higher dose. Liver impairment was the most frequently observed toxicity. The homozygous genotype was associated with a significantly higher incidence of hepatic toxicity for both the SLC19A1 (P = 0.037) and TS (P = 0.002). Logistic regression analysis indicated an increased risk of vomiting for the 2R/3R genotype of the TS gene (OR 3.20, 95% CI 1.33–7.68, P = 0.009) and for vomiting and hepatic toxicity for the 3R/3R genotype (vomiting: OR 3.39, 95% CI 1.12–10.23, P = 0.031; liver toxicity: OR 2.28, 95% CI 1.05–4.95, P = 0.038). None of the acute toxicities differed between the analyzed dosing groups. Conclusions: Determination of polymorphisms of SLC19A1, MTHFR, and TS genes might allow for a better prior selection of patients with higher risk of elevated Mtx levels. Our study is the first one to report the increased risk of hepatotoxicity and vomiting in patients with TS polymorphisms.